Investigating the Relationship Among the Construction Safety Plan, Knowledge Management, Audit Process, Information System, Web, and BIM with Construction Safety Performance - Fadli, Zafira Alysha; Latief, Yusuf; Nugroho, Danang Budi (CSID Journal of Infrastructure Development, 2024)
The rapid growth of high-rise building construction in Indonesia has led to a significant increase in accidents, necessitating a robust audit process for construction safety. This research investigates the relationship between construction safety plans (CSPs), audit processes, knowledge management (KM), information systems, the web, and BIM on construction safety performance, aiming to develop a BIM-based KM audit process. To analyze the significance level of various indicators for each variable considerable importance, a mixed-methods approach was employed, combining qualitative insights from expert interviews with quantitative analysis using Structural Equation Modeling (SEM) via SmartPLS. The findings in the study reveal that the studied variables have a Cronbach's Alpha value above 0.7, and the retained variables have a significant value greater than or equal to 0.7. In this study, the confidence level is 95%, where there is a relationship between variables that meet the t-table, which is > 1.96, it can be concluded that the relationship between each variable has a significant value. This study provides a framework for integrating these elements to enhance construction safety performance, offering valuable guidelines for industry stakeholders to improve safety practices in construction projects.